Satisfaction with life and job satisfaction - Cardoza Sernaqué, Manuel Antonio (2019)
In the field of human talent management systems, the study of satisfaction with life has become a very significant construct to understand how the subjective aspects of the human person, that is, their personal, family, social situation and citizen influences job satisfaction experienced by people. In this context, the research aimed to determine the relationship between satisfaction with life and job satisfaction of administrative employees in a private university in the city of Chimbote. The research, according to its scope, is of a correlational descriptive type, with a non-experimental design and its transverse temporality. The study sample consisted of 130 collaborators, 51 belonged to the female sex and 79 to the male. The information was collected through two questionnaires: the first to measure satisfaction with life, adapted of Alama, Motosono y Ramos (2016), and the second. The Labor Satisfaction by Ruiz, Zavaleta y Ruíz (2017). With the use of the rho Spearman test, it was found that the level of satisfaction with life is medium (55%) and job satisfaction presents a medium level (66.9%). Finally, it was found that there is a high positive relationship (r = 0.765) significant (p <0.05) between satisfaction with life and job satisfaction of administrative employees of a private university in the city of Chimbote, that is, t greater satisfaction with life, higher job satisfaction.